2016
DOI: 10.1016/j.ejmech.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Novel hederagenin–triazolyl derivatives as potential anti-cancer agents

Abstract: A series of novel aryl-1H-1,2,3-triazol-4-yl methylester and amide derivatives of the natural product hederagenin was synthesized aiming to develop new antitumor agents, using Huisgen 1,3-dipolar cycloaddition reactions, with yields between 35% and 95%. The structures of all derivatives (2-31) were confirmed by MS, IR, (1)H NMR and (13)C NMR spectroscopic data. The cytotoxic activities of all compounds were screened against a panel of six human cancer cell lines using SRB assay. It was found that most of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…There was no indicationo ft he presence of the syn-bromo isomer 5,a nd presumably the outcome is dictated by ap reference for the bromine to approach the intermediate benzylic radical anti to the fluorines.I tw as attractive to introduce an amine at the benzylic position of 2,a nd to this end displacement of the bromide by azide in DMF was explored. [15] However this resulted in an efficient conversion only to tertiary alcohol 6 (Scheme 2). This outcomew as unexpected, and after a series of control reactions it emerged that heating (90 8C) in DMF alone, without added sodium azide,w as sufficient to mediate the conversion.…”
Section: Resultsmentioning
confidence: 99%
“…There was no indicationo ft he presence of the syn-bromo isomer 5,a nd presumably the outcome is dictated by ap reference for the bromine to approach the intermediate benzylic radical anti to the fluorines.I tw as attractive to introduce an amine at the benzylic position of 2,a nd to this end displacement of the bromide by azide in DMF was explored. [15] However this resulted in an efficient conversion only to tertiary alcohol 6 (Scheme 2). This outcomew as unexpected, and after a series of control reactions it emerged that heating (90 8C) in DMF alone, without added sodium azide,w as sufficient to mediate the conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that introduction of nitrogen‐containing moiety at C‐6 position based on the scaffold of 4 afforded compound 6 may improve drug‐like properties and antiproliferative activities . In addition, triazoles have been proved to possess various pharmacological properties including anti‐infective, anticancer, antiviral, and antihypertensive activities . Based on the above‐mentioned results and our initial studies, we directed our chemical modification on C‐5 and C‐6 positions through introduction of different kinds of moieties including various nitrogen‐containing or triazole moieties (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…4 In recent years, HG has been observed to be biologically active, as well as many other saponins with similar structures, such as ursolic acid and corosolic acid. HG exhibits multiple pharmaceutical and biological activities, including antitumor, 2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] anti-inammatory, [24][25][26][27][28][29][30] anti-depressant, [31][32][33][34][35] antineurodegenerative, [36][37][38] anti-hyperlipidemia, 4,39,40 anti-diabetic, [41][42][43] anti-leishmanial, 19,44,45 and anti-viral (against hepatitis B) activity. 46 Recently, a number of studies have investigated the use of HG as a potential anti-tumor agent.…”
Section: Introductionmentioning
confidence: 99%
“…46 Recently, a number of studies have investigated the use of HG as a potential anti-tumor agent. 5,6,[10][11][12][14][15][16] The pharmacokinetics, [47][48][49][50][51] structural modication, [17][18][19][20][21]35,38,45,46 and mechanisms of action [4][5][6][10][11][12][13][14][15][16]19,25,26,[31][32][33][34]36,37,39,40,43,45 of HG have also been studied. However, possibly owing to limited in vivo data, HG is still in the preclinical development stage.…”
Section: Introductionmentioning
confidence: 99%